BECOMING CHRISTIAN, REMAINING MALAY: A Study of Religious Inculturation among Malay Christians - Suheri Suheri; Ahmad Alif Amin; Maftukha Maftukha (Institute for Southeats Asian Islamic Studies (ISAIS)Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
This study explores the dynamics of religious identity and cultural adaptation among Malay Christians, a minority community living within the dominant Malay-Islamic culture in the coastal regions of Sumatra, specifically in Riau. The research aims to understand how these Christians negotiate their faith and cultural belonging without perceiving religion and culture as opposing entities. Data were collected through interviews, participant observation, and document analysis of the Malay Christians community. The findings reveal that they not only adopt Christian theology but reinterpret it within the Malay cultural framework. This process manifests in various expressions, such as the use of Malay language in worship, the emphasis on politeness (sopan santun) and communal solidarity (gotong royong), and active participation in interfaith social engagements. The study concludes that Malay Christians exemplify an ongoing process of religious inculturation in Indonesia, where faith and culture coexist and mutually enrich one another. Their religious identity emerges from dynamic social interactions and deep spiritual reflection on local traditions, offering a meaningful contribution to inclusive and civilized interfaith dialogue in Indonesia.